THE BEHAVIOR OF URBAN COMMUNITIES IN PLANTING USEFUL PLANTS IN THE YARD DURING COVID-19 PANDEMIC - Novriyanti Novriyanti; Dian Iswandaru; Inggar Damayanti (Media Konservasi, 2021)
Corona Virus Disease (COVID-19) pandemic that forces restrictions on movement between people is thought to impact the utilization of yards in urban areas positively. However, there is not much information about yard management practices, including plant species managed by urban communities. In the framework of biodiversity conservation, this research aims to explore the variety of plant species planted in the yards, the area of ​​managed yards, and the planting motivation of the urban community, especially during the COVID-19 pandemic. The research was conducted from May to August 2020 using an online questionnaire (Google Form), and direct interviews with target respondents consisted of communities spread across two major cities in Lampung Province, i.e. Metro City and Bandar Lampung City. The research findings showed that only 8% of respondents planted various useful plant species during the COVID-19 pandemic, while the rest of them planted long before the pandemic occurred. The plant groups that the respondents commonly owned were ornamental plants (70%), while 30% of the existing species were medicinal plants and spices. The motivations included enjoying the yield (herbs and medicine), filling the spare time, enjoy gardening and love plants, making the house beautiful and cool, and even planting it for sale. Of the five planting goals or motivations of the urban community, the motivation to enjoy the yield was the highest, followed by the desire to have a beautiful yard and enjoy gardening. This condition is believed to continue to exist even though modernization is expanding. Keywords: COVID-19 pandemic, ethnobotany, ornamental plants, residential landscape, useful plants